(untitled) (Journal of Informatics Education and Research, 2025)
The case study discusses the challenges faced by Namdhari Seeds Pvt. Ltd., a leading seed company in India, in optimizing its reverse logistics operations. The company has witnessed a high rate of seed returns, ranging from 9% to 16.3% over the past few years, which has had a significant impact on the company’s profitability and operations. The key issues identified include the bullwhip effect in the supply chain, financial implications of reverse logistics, data management and traceability challenges, product quality and viability concerns, and the impact of seasonality on timely processing of returns.